Welcome to the Brave New World: CRISPR Mediated Genome Editing?pathway to Designer Babies? - Elizondo, Diana; Fernando, Lourds Michelle; Oliver, Everett; Clinton, Keely; Retland, Nicole; Paturault, Henri; Ullah, Hemayet (Plant Tissue Culture and Biotechnology, 2015)
Abstract not available Plant Tissue Cult. & Biotech. 25(1): 143-154, 2015 (June)